Qualidade fisiológica de sementes de Jatropha curcas L.: efeito de embalagens, ambientes e períodos de armazenamento - Pinto Junior, Artur Soares (2010)
Seeds of physic nut (Jatropha curcas L.) have characteristics Orthodox and require knowledge about the factors that affect the maintenance of their physiological quality. The objective of this study was to evaluate and identify the suitable condition for the storage of seeds of physic nut (J. curcas L.). The seeds were stored for periods of 90 and 180 days in packages consisting of different materials: transparent plastic of low density, with 0.06 mm thick Kraft paper bags, natural 40 g m-2, and packaging glass with a capacity of 500 mL. These were kept in three different environments: laboratory, without control of environmental conditions (10 to 29 ° C, 50 to 98% relative humidity.), Refrigerator (4 to 6 ° C, 35 to 43% RH) and air chilled (14 to 16 ° C and 75 to 80% relative humidity), obtained with use of an air conditioner and a dehumidifier. For the experiment, based on a combination of treatments provided, we used a completely randomized design with four replications in a factorial (3x3 +1), and the factors consisting of three packs, three environments and initial assessment of material under study (control). At the beginning and after periods of storage the seeds were tested for moisture content, germination, first count, germination and tetrazolium test in the laboratory. Also evaluated in a greenhouse environment (50% shading) the germination rate and speed of germination and after 45 days of onset of seedling emergence were performed morphological destructive. The average values for moisture content, first count, germination and tetrazolium test differ in the respect of packaging and storage environments. The same was true for tests for the index rate of emergence, germination, dry masses of root, shoot and total root / shoot, plant height and basal diameter and Quality Index Dickson. However, seeds stored in a glass container and refrigerator environment showed better maintenance of their physiological characteristics and quality and can be stored for a period of six months without a reduction of the physiological quality